Assessment of Wash Practices in Detention Centres (American Journal of Multidisciplinary Research and Innovation, 2025)
Detention centres are places where accuse or convicted individuals are confine pending the conclusion of investigation and prosecution or as decided by a court of Law in line with the constitution of the country. Water Sanitation and Hygiene practice is fundamental to health and should be accessible to all including individuals in detention. The sanitary condition of detention centres is devastating and sometime allowed to serve as punishment ground. This condition is bothersome as the world is stressing on the provision of WASH services for all irrespective of the environment to minimise the spread of communicable diseases. Descriptive research design was employed. The area of the study was Maiduguri the capital city of Borno State, Nigeria. The population of the study are accused/convicted individuals and individuals working in detention centres. Judgemental sampling technique was used in determining the sample size of 192 (96%). Semi-structured questionnaire was used to obtain data on the hygiene practice of detainees and their environment while in detention. The data was analysed using Microsoft Excel 2019 and presented using frequency counts, percentage on table. The findings revealed (n=131, 68.23%) utilize pit latrines, poor handwashing facilities, infrequent bathing, and inadequate cell cleaning. Majority of respondents (60.94%, n=117) reported that detainees do not have access to safe drinking water, (63.02%) described the hygiene condition of the detention cells as poor, while 14.06% described it as very unhygienic. These findings underscore the need for improved WASH infrastructure and practices in detention centers to promote a healthier environment for detainees.